Kaji eksperimental mesin pirolisis distilasi asap pembakaran sampah plastik menjadi bahan bakar alternatip dengan menggunakan direct cooling coil - Lukitobudi, Arda Rahardja (ReTII, 2021)
The property of plastic which is durable, light and heat resistant make plastic use more increasingly. But the plastic waste has big impact to the environment due to hard to decompose. Plastic waste distillation by pyrolysis method could be one of how to reduce the plastic waste. Plastic waste can be processed into alternative fuel more useful. The distillation rig consist of 2 kg LDPE plastic waste reactor equipped with pyrolysis tube with spiral coil inside of 4x1.4 m. The spiral coil inside the pyrolysis tube as direct cooling coil flowed by propylene glycol with 5 temperature variations, -9°C, -3°C, 3°C, 9°C and atmospheric temperature. The cooling process done by brine cooling machine. Burning process using fire stove of ±400°C with 3kg LPG. Distillation process using refrigeration system produce more alternative fuel compared to pyrolysis process without refrigeration system. On secondary refrigerant temperature of -9°C, -3°C, 3°C, 9°C and without refrigeration system, produce alternative fuel of 1920 mL, 1290 mL, 1050 mL, 630 mL, 430 mL. Keywords: Pyrolysis, plastic waste, alternative fuel, brine cooling, direct cooling coil, LDPE.